The never never sisters - Heller, L. Alison (New American Library, 2014)
" An absorbing, highly entertaining novel about family secrets, The Never Never Sisters introduces you to the strong-willed and big-hearted Reinhardt women, as they reunite one summer in New York. Gifted storyteller L. Alison Heller has written another witty and moving page-turner that will captivate readers and keep them guessing right up until the satisfying end. Sometimes you just need to get away. Marriage counselor Paige Reinhardt is counting down the days to summer, eager to reconnect with her workaholic husband at their cozy rental cottage in the Hamptons. But soon a mysterious crisis at Dave's work ruins their getaway plans. Paige is still figuring out how to handle the unexplained chill in her marriage when her troubled sister suddenly returns after a two-decade silence. Now, instead of enjoying the lazy summer days along the ocean, Paige is navigating the rocky waters of a forgotten bond with her sister in the sweltering city heat. As she attempts to dig deeper into Dave's work troubles and some long-held family secrets, Paige is shocked to discover how little she knows about the people closest to her. This summer, the self-proclaimed relationship expert will grapple with her biggest challenge yet: Is it worth risking your most precious relationships in order to find yourself?"--